Research on the Effects of Occupational Stress and the DRD2 Gene on the Psychological Health of Workers in the Xinjiang Desert Oil Field - Jiang, Ting; Wumaier, Gulijianati; Li, Xue; Yang, Xu; Liu, Jiwen (Frontiers in Psychiatry, 2021)
Background: This study investigated the relationship between occupational stress and the mental health of people working in oil fields in the arid desert environment of Xinjiang Methods: The participants of this study included oil field company workers from the Xinjiang Petroleum Administration of Karamay City, Xinjiang, who underwent occupational health examinations. The Occupational Stress Inventory Revised Edition (OSI-R) was used to measure the occupational stress of the oil workers. The mental health status of oil workers was evaluated using the Symptoms Checklist-90. Results: Occupational tasks, the total scores of the personal strain and mental health questionnaires were positively correlated with somatization, obsessive-compulsive symptoms, interpersonal sensitivity, depression, anxiety, hostility, terror, paranoia, and psychosis (P<0.05). Individual coping resources and the mental health total score was negatively correlated with somatization, obsessive-compulsive symptoms, interpersonal sensitivity, anxiety, hostility, terror, paranoia, and psychosis. The following factors were identified as mental health risk factors: female gender; age 45 and above (relative to≤30 years old); high scores on the personal strain questionnaire; occupational stress; external effort; internal investment; and high effort-low return. The following factors were identified as protective factors for mental health: Han nationality; oil transportation (relative to drilling); individual resilience; and work returns. In respect to the abnormal psychological group and the normal psychological group, statistically significant differences were found in the distribution of genotypes and allele frequencies at the rs1800497 locus (P<0.05). Conclusions: This study shows that occupational stress and the D2 dopamine receptor (DRD2) gene have an impact on the mental health of oil field workers in the arid desert environment of Xinjiang. Effort-reward imbalance and occupational stress were identified as risk factors for mental health, while rewards for work were protective factors. Higher levels of occupational stress may lead to depression and other psychological disorders, adversely affecting mental health. In oil field operators in the arid desert environment of Xinjiang, the AA genotype of the DRD2 gene in the rs1800497 locus was identified as a genotype specific to susceptibility to mental health problems, and a correlation was found between the A allele and an increased risk of psychological problems.